A Study of Priority Sector Advances of Commercial Banks in India - Selvakumar, M.; Kathiravan, P. G. (Indian Journal of Finance, 2009)
Socialisation of bank credit has been the theme of priority sector lending by the commercial banks. Since the public sector banks touch the lives of millions, it is their top most responsibility to help the government in achieving the different socio-economic priorities like growth of agriculture, small-scale industries, exports, raising employment levels, encouragement of entrepreneurs and development of backward areas.After nationalisation of banks, lending to priority sector was seen as an essential component of national agenda. Starting from the year 1969, there was only a single target for priority sector lending till the end of 1970’s. In the mid 1970’s, RBI advised banks to raise the proportion of credit to the priority sector to 33.3 per cent by March, 1979. This target was gradually raised to 40 per cent which was to be achieved by March 1985.Priority sector included agriculture (direct and indirect) SSI’s and industrial estates, road and water transport operators, retail trade, small business professional and self -employed persons and education. In the year 1980, on the basis of recommendations of Krishnaswamy, weaker section (small and marginal farmers, landless labourers, SC/ST and so on) were also included in the priority sector. The Ghosh Group (1982) made important recommendations regarding the nature of agriculture advances and targeting of direct and indirect farm lending. Minimum agriculture credit was to be fixed at 14 per cent of net bank credit and in view of the increasing credit flow for farming operations, it was raised to 16 per cent by March, 1987, 17 per cent by March, 1989 and to 18 per cent by March, 1990.